DAMPAK TEKNOLOGI INFORMASI PADA PERCIEVED USEFULNESS DARI PENGAMBILAN KEPUTUSAN - Ade Widiyanti (Jurnal Akuntansi dan Keuangan (JAK), 2023)
The preparation of regional budgets is influenced by many factors, so the decision-making must be careful and thorough and supported by adequate data sources. However, human resources also have limitations in storing and remembering the data needed for making budgetary decisions. The preparation of government financial statements currently uses the accrual basis, so that more and more data will be available. Information technology support can reduce the gap between the capabilities of human resources and the demands of budget decisions. This study aims to examine and analyze the effect of information technology support on the perceived usefulness of decision making and its implications for the quality of accrual-based accounting. The object of this research is the government of Lampung Province. The population used is the entire Lampung Provincial Government, while the sample used in this study is the Lampung Provincial Government SKPD. The data was obtained through the distribution of questionnaires to the respondents, namely the SKPD of the Lampung Provincial Government. The data was analyzed using structural equation modeling (SEM) with Lisrel software. This study uses primary data by using a questionnaire as a research instrument. The output of this research is expected to be published in Scopus indexed international journals or national journals (SINTA-3) and the results of this study are expected to be taken into consideration by the government in improving its regional financial performance and realizing financial management accountability in government in Indonesia.